Design, verification and validation of a dynamic model for an intramuscular autoinjector - Magubane, Ntokozo (Department of Human Biology, 2025)
The rising prevalence of autoimmune and chronic conditions is a concern worldwide, leading to a need for disease management therapies to aid medication adherence and compliance. Autoinjectors are prime medical devices used to inject antidotes and prophylactics into the intramuscular or subcutaneous layer. These devices are used in various autoimmune and chronic conditions to counteract opioid overdose and nerve gas poisoning. There are easy to use and often allow for self-administration of medication. The development of new injectable molecules for different diseases and the reformation of first-generation pharmaceuticals has led to growing interest in making autoinjectors usable for different medications. The major challenge in this quest is the complexity of injecting highly viscous drugs and in large volumes. This research aims to develop a dynamic model to describe the influence of drug viscosity and volume on the injection process and evaluate the sensitivity of medication fluid behaviour to variations in component dimensions of the autoinjector fluid delivery system. Using mathematical modelling, the kinematic properties relating to the plunger motion were modelled and verified through physical testing. This model was optimised via the evaluation of sensitivity and measuring the results against the validation results. A Computational Fluid Dynamics (CFD) study was conducted to analyse the fluid behaviour of different viscous medications. This study allowed for the variation of fluid viscosity, medication volume, needle gauge and length. The computational model was then verified and validated using the American Standard of Mechanical Engineers Verification and Validation Standards (ASME V&V 40 and V&V20). This was accompanied by fluid characterisation of four medications, namely adrenaline, amikacin, Vaxigrip and insulin basaglar using a rheometer. The ZwickRoell universal tester measured the syringe force and plunger displacement to derive the pressure changes. These results were evaluated against the computational model. According to the optimised mathematical model and validation results, the plunger displacement increases linearly when the plunger motion is initiated until a maximum displacement is reached. Separation flow was observed in the syringe for viscosities between 15 - 80 cP. This represents decreasing flow as pressure increases in the syringe for medications with a viscosity in this range. This phenomenon increases the chances of needle deformation and injection pain due to tissue damage. High-gauge needles are more effective for injecting lower volumes and low viscosity medications, while low-gauge needles work best for injecting larger volumes or highly viscous medications. The model risk is defined to be high according to the ASME guidelines. If the model results directly impact the autoinjector design without any further testing to inform the design process, an incorrect model would result in poor-performing autoinjectors that fail to deliver the desired dose of medication into the intramuscular layer at the required injection time. This research has proved that it's possible to inject highly viscous drugs and large doses using an autoinjector if the right balance of injection force, injection time and needle dimensions is carefully selected to improve compliance and patient experience.